Long Non-coding RNA SNHG17 Promotes Cell Proliferation and Invasion in Castration-Resistant Prostate Cancer by Targeting the miR-144/CD51 Axis - Bai, Minghua; Lei, Yutiantian; Wang, Mincong; Ma, Jinlu; Yang, Pengtao; Mou, Xingyi; Dong, Yiping; Han, Suxia (Frontiers in Genetics, 2020)
Previously, we found that the expression of long non-coding RNA (lncRNA) small nucleolar RNA host gene 17 (SNHG17) was up-regulated in castration-resistant prostate cancer (CRPC) cells compared to that in hormone sensitive prostate cancer (HSPC) cells. Moreover, we found that CD51 was up-regulated in prostate cancer cells and promoted the carcinogenesis and progression of prostate cancer. However, the regulatory mechanism of SNHG17 and CD51 in the development of CRPC remains unclear. In the current study, we aimed to elucidate the expressions, functions, and underlying mechanism of SNHG17 and CD51 in CRPC. Our results further confirmed that both SNHG17 and CD51 were up-regulated in CRPC tissues and cells. In addition, we found that SNHG17 expression was positively correlated with CD51 expression in prostate cancer. Mechanically, SNHG17 functioned as a competing endogenous RNA (ceRNA) to up-regulate CD51 expression through competitively sponging microRNA-144 (miR-144), and CD51 was identified as a direct downstream target of miR-144 in CRPC. Functionally, down-regulation of SNHG17 or up-regulation of miR-144 inhibited the proliferation, migration, and invasion of CRPC cells, whereas up-regulation of SNHG17 and down-regulation of miR-144 promoted the proliferation, migration and invasion of CRPC cells in vitro and in vivo. Using gain and loss-of function assay and rescue assay, we showed that miR-144 inhibited cell proliferation, migration and invasion by directly inhibiting CD51 expression, and SNHG17 promoted cell proliferation, migration and invasion by directly enhancing CD51 expression in CRPC cells. Taken together, our study reveals the role of the SNHG17/miR-144/CD51 axis in accelerating CRPC cell proliferation and invasion, and suggests that SNHG17 may serve as a novel therapeutic target for CRPC.